Characterization of Immune Cells from Adipose Tissue. (24th July 2019) - Bapat, Sagar P.; Liang, Yuqiong; Zheng, Ye
Abstract: Adipose tissue (AT) serves a crucial role in maintaining organismal metabolic homeostasis. Studies have demonstrated that AT is populated with a diverse array of immune cells that coordinate and regulate AT function. This adipo‐immune system is highly dynamic, reflecting the physiologic state of the organism (e.g., obese, lean, aged, or young) as well as the constant physiologic remodeling of AT associated with the daily rhythms of fasting and feeding. Many of the adaptive and maladaptive functional changes of AT are regulated by changes in the quantity and quality of distinct sets of AT‐resident immune cells. Here we present protocols to assess the dynamic state of the immune system within AT by constructing censuses of adipose‐resident immune cells (macrophages, dendritic cells, neutrophils, eosinophils, NK cells, innate lymphocytes, T cells, and B cells, etc.) based on flow cytometry, which we term adipo‐immune profiles (AIPs). Constructing AIPs can be an integral part of assessment for AT health and function. This article describes the protocols to generate such AIPs. © 2019 by John Wiley & Sons, Inc.